The Marketplace of Aid in Africa. Choice in Critical Conditions - Mah, L.; Freitas, R. (Les Cahiers du Centre Émile Durkheim, 2014)
he paper will explore the impact of emerging donors within the marketplace of aid vis-à-vis the traditional donors and its efects on the possibilities for Sub-Sahara African countries to define and afirm autonomous policy positions on the basis of their national development interests. We first identify the changing relations in the development aid landscape and the contours of the marketplace of aid. We then analyse the consequences of the changes and the impacts on policy space. We conclude that the shit in emphasis from the notion of development aid to a notion of development cooperation broadens the range of financing mechanisms and also the degree of leverage for autonomous policy-making vis-a-vis its partners. he extent to which Sub-Saharan Africa will be able to muster this potential to its own beneit depends largely on leadership and governance issues.